2021
DOI: 10.20546/ijcmas.2021.1010.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Growth Parameters on Carpobrotus edulis, Kalanchoe daigremontiana and Kalanchoe tubiflora in Relation to Different Seaweed Liquid Fertilizer (SLF) as a Biostimulant

Abstract: The aim of this research was to evaluate the biofertilization capacity of five different species of algae, representative of the three main groups of macroalgae selected from Lake Ganzirri in Messina, Venice Lagoon and Norwegian coasts. The experiments, started in January 2021, were conducted in the greenhouses of CREA-OF in Pescia (Pt), Tuscany, Italy (43°54′N 10°41′E) on Carpobrotus edulis, Kalanchoe daigremontiana and Kalanchoe tubiflora from seed. The test showed a significant increase in the agronomic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The main reason why Chlorella can grow rapidly is because it contains Chlorella Growth Factor (CGF), which is quite rich in nucleoproteins, nucleic acids, ribonucleic acids (RNA), deoxyribonucleic acids (DNA), vitamins, amino acids, polysaccharides, complex protein bodies, enzymes, glycoproteins, plant hormones, etc. Its ability to promote plant growth may be due to this factor [15,[17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…The main reason why Chlorella can grow rapidly is because it contains Chlorella Growth Factor (CGF), which is quite rich in nucleoproteins, nucleic acids, ribonucleic acids (RNA), deoxyribonucleic acids (DNA), vitamins, amino acids, polysaccharides, complex protein bodies, enzymes, glycoproteins, plant hormones, etc. Its ability to promote plant growth may be due to this factor [15,[17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…These processes can vary as a function of the ionic species and the pH and EC of the substrate [ 1 , 55 ]. It has been shown that during the vegetative period, tomato plants require mainly N, followed by K, P, Ca, Mg, and S [ 37 , 38 ]. Previous studies agree with our results and have reported increases in macro- (N, P, K, Mg, and Ca) and micronutrient (Zn, Cu, Fe, and Mn) concentrations following Ulva spp.…”
Section: Resultsmentioning
confidence: 99%
“…Ulva ohnoi has also been successfully grown under different culture conditions and in intensive systems, which has resulted in the stable and commercial production of biomass [ 34 , 35 ]. However, few studies have evaluated the agricultural potential of this species [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…After sampling, biomasses were transported in chilled condition after cleaning by washing in fresh water and drying in an oven at 40 • C for 48 h until extraction. For the preparation of Liquid Seaweed Fertilizer (LSF), dried macroalgae were prepared with the modified protocol from Rama (1990) [1]; the process is described in detail in Spagnuolo and Prisa (2021) [2]. In summary, each solution was prepared with 500 mL of distilled water and 25 g of dried seaweed (ratio 1:20 DW/V) at 80 • C for three hours.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropic processes act as one of the prominent effects accentuated by climate change. Consequently, drought events are increasing, causing a relevant loss in crop yield and water availability for cultivation [1,2]. Considering this, improving resistance ability and agricultural production is vital, and is a challenging task, but is needed to meet the growing food demand due to population growth [3].…”
Section: Introductionmentioning
confidence: 99%